Mitonuclear Mismatch is Associated With Increased Male Frequency, Outcrossing, and Male Sperm Size in Experimentally-Evolved C. elegans - Bever, Brent W.; Dietz, Zachary P.; Sullins, Jennifer A.; Montoya, Ariana M.; Bergthorsson, Ulfar; Katju, Vaishali; Estes, Suzanne (Frontiers in Genetics, 2022)
We provide a partial test of the mitonuclear sex hypothesis with the first controlled study of how male frequencies and rates of outcrossing evolve in response to mitonuclear mismatch by allowing replicate lineages of C. elegans nematodes containing either mitochondrial or nuclear mutations of electron transport chain (ETC) genes to evolve under three sexual systems: facultatively outcrossing (wildtype), obligately selfing, and obligately outcrossing. Among facultatively outcrossing lines, we found evolution of increased male frequency in at least one replicate line of all four ETC mutant backgrounds tested—nuclear isp-1, mitochondrial cox-1 and ctb-1, and an isp-1 IV; ctb-1M mitonuclear double mutant—and confirmed for a single line set (cox-1) that increased male frequency also resulted in successful outcrossing. We previously found the same result for lines evolved from another nuclear ETC mutant, gas-1. For several lines in the current experiment, however, male frequency declined to wildtype levels (near 0%) in later generations. Male frequency did not change in lines evolved from a wildtype control strain. Additional phenotypic assays of lines evolved from the mitochondrial cox-1 mutant indicated that evolution of high male frequency was accompanied by evolution of increased male sperm size and mating success with tester females, but that it did not translate into increased mating success with coevolved hermaphrodites. Rather, hermaphrodites’ self-crossed reproductive fitness increased, consistent with sexually antagonistic coevolution. In accordance with evolutionary theory, males and sexual outcrossing may be most beneficial to populations evolving from a state of low ancestral fitness (gas-1, as previously reported) and less beneficial or deleterious to those evolving from a state of higher ancestral fitness (cox-1). In support of this idea, the obligately outcrossing fog-2 V; cox-1 M lines exhibited no fitness evolution compared to their ancestor, while facultatively outcrossing lines showed slight upward evolution of fitness, and all but one of the obligately selfing xol-1 X; cox-1 M lines evolved substantially increased fitness—even beyond wildtype levels. This work provides a foundation to directly test the effect of reproductive mode on the evolutionary dynamics of mitonuclear genomes, as well as whether compensatory mutations (nuclear or mitochondrial) can rescue populations from mitochondrial dysfunction.